Collective action for market-chain innovation in the Andes - Devaux, André; Horton, Douglas; Velasco, Claudio; Thiele, Graham; López, Gastón; Bernet, Thomas; Reinoso, Iván; Ordinola, Miguel (International Food Policy Research Institute, 2016)
Chapter 7 (Devaux et al.) analyzes the work of the International Potato Center’s (CIP) Papa Andina regional network in Bolivia, Ecuador, and Peru. This work sought to capitalize on the genetic diversity of native potatoes grown in remote mountainous areas, as well as on the social capital and local knowledge of the smallholders who have cultivated them for centuries—assets that are often undervalued. An action–research approach, known as the Participatory Market Chain Approach (PMCA), was developed, which engages smallholders, market agents, researchers, and agricultural service providers to jointly identify market opportunities and to foster the commercial, technological, and institutional innovation needed to exploit these opportunities. This approach, developed and first applied in potato value chains in the Andes, has now been shared, tested, and applied successfully in other value chains and other regions (Mayanja et al. 2012; Horton et al. 2013).